Linking Cell Cycle to Asymmetric Division: Aurora-A Phosphorylates the Par Complex to Regulate Numb Localization - Wirtz-Peitz, Frederik (2008)
Drosophila neural precursor cells divide asymmetrically by segregating the Numb protein into one of the two daughter cells. Numb is uniformly cortical in interphase but assumes a polarized localization in mitosis. Here, we show that a phosphorylation cascade triggered by the activation of Aurora-A is responsible for the asymmetric localization of Numb in mitosis. Aurora-A phosphorylates Par-6, a regulatory subunit of atypical protein kinase C (aPKC). This activates aPKC, which initially phosphorylates Lethal (2) giant larvae (Lgl), a cytoskeletal protein that binds and inhibits aPKC during interphase. Phosphorylated Lgl is released from aPKC and thereby allows the PDZ domain protein Bazooka to enter the complex. This changes substrate specificity and allows aPKC to phosphorylate Numb and release the protein from one side of the cell cortex. Our data reveal a molecular mechanism for the asymmetric localization of Numb and show how cell polarity can be coupled to cell-cycle progression.